Transport Time and Mortality in Critically Ill Patients with Severe Traumatic Brain Injury. (12th November 2021) - Sy, Eric; Amram, Ofer; Baer, Heather J.; Hameed, S. Morad; Griesdale, Donald E.G.
ABSTRACT: Purpose: Severe traumatic brain injury (TBI) is a major cause of morbidity and mortality in critically ill patients. Pre-hospital care and transportation time may impact their outcomes. Methods: Using the British Columbia Trauma Registry, we included 2, 860 adult (≥18 years) patients with severe TBI (abbreviated injury scale head score ≥4), who were admitted to an intensive care unit (ICU) in a centre with neurosurgical services from January 1, 2000 to March 31, 2013. We evaluated the impact of transportation time (time of injury to time of arrival at a neurosurgical trauma centre) on in-hospital mortality and discharge disposition, adjusting for age, sex, year of injury, injury severity score (ISS), revised trauma score at the scene, location of injury, socio-economic status and direct versus indirect transfer. Results: Patients had a median age of 43 years (interquartile range [IQR] 26–59) and 676 (23.6%) were female. They had a median ISS of 33 (IQR 26–43). Median transportation time was 80 minutes (IQR 40–315). ICU and hospital length of stay were 6 days (IQR 2–12) and 20 days (IQR 7–42), respectively. Six hundred and ninety-six (24.3%) patients died in hospital. After adjustment, there was no significant impact of transportation time on in-hospital mortality (odds ratio 0.98, 95% confidence interval 0.95–1.01). There was also no significant effect on discharge disposition. Conclusions: No association was found between pre-hospital transportation time and in-hospital mortality in critically ill patients with severe TBI.